Potensi Tanaman Lokal sebagai Tanaman Biofarmaka untuk Kesehatan di Desa Lemahbang dan Desa Pucung, Kecamatan Kismantoro, Kabupaten Wonogiri - Purwanta; Jauharah Rafagusta Suhendar; Aida Firzana, Afifah Nur (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
The use of traditional medicine utilizing herbal plants has become a familiar part in Indonesian culture. Herbal plants are known for their healing properties and ability to prevent various diseases. Many of these herbal plants, which have the potential to be developed into biopharmaceutical plants, can be found in Lemahbang Village and Pucung Village, Kismantoro District. However, the utilization of herbal plants in Lemahbang and Pucung Villages remains limited, primarily used as kitchen spices or traditional herbal drinks (jamu). Therefore, further development is necessary to enhance the potential of these herbal plants into biopharmaceuticals.This community service activity is divided into three phases: 1) preparation phase; 2) implementation phase; and 3) evaluation phase. These phases were conducted from December 2023 to January 2024. The activities introduced the preparation of turmeric and tamarind powder and aloe vera soothing gel. The outcomes of this activity include the production of these herbal products, data on herbal plants in Lemahbang Village, digitization of data, and a booklet listing the herbal plants found in Lemahbang Village.The conclusion drawn from this activity is that it has the potential to increase the community's knowledge and awareness of the local herbal plants' potential, thereby enhancing the health and economic benefits for the community. The digitization process through the village website provides easier access for the community to obtain information about herbal plants. Practical training also directly benefits PKK members in processing simple herbal products.